Revisiting Palmares: stories of a mocambo in colonial Brazil - Viotti, Ana Carolina [UNESP] (Univ Antioquia, 2017)
In this article the reader Is invited to revisit the multiple narratives on Palmares, the best known Brazilian colonial mocambo. Based on various accounts - letters, travel journals and administrative documents - the article shows the exemplar character of the destruction of these slave gathering, highlighting the most striking nuances in the various reports on the mocambo. The article also presents the mayor historiographical debates on these slave gatherings, illustrating the plural readings on Palmares.
Keywords: mocambos; quilombos; Palmares; colonial Brazil; slave rebellion